33. Efficacy of Jatropha(Jatrophacurcas L.) Sap Cream in Inflammation Phase of Wound Healing on Mice Skin - Hidayati Hidayati; Muhammad Nur Salim; Ummu Balqis; Dian Masyitha; Cut Dahlia Iskandar; Darmawi Darmawi; Abdul Harris (Jurnal Medika Veterinaria, 2019)
This study aim to know the efficacy of the jatropha sap cream toward the inflammatory phase of wound healing on the skin of mice. This study used 9 male mice, with 25-40 grams weights and 2-3 months old.  Male mice receiveddivided into 3 groups, and3 deuteronomy.The cut is done in the back as 2 cm long. Wound care is done twice a day at 08.00 am and at 18.00 pm for 3 days. The treatment I (PI) cuts smeared a cream base (as a negatif control); treatment II (PII) smeared 10% jatropha sap cream; and the treatment III (PIII) smeared 0.1% sulfadiazine  (as a positive control).Created a skin sample preparation microtechnic stained with hematoxylin-eosin (HE). The result on the number of infiltration of inflammatory cells and neovascular on PI; PII; and PIII were 402,00 ± 7,21 and 14,00 ± 5,57; 248,67 ± 1,53 and 34,67 ± 7,51; and 343,00 ± 8,89 and 28,00 ± 5,00  (P0,01). Based on the result it be concluded the treatment of 10% jatropha sap cream can speed up the process of the inflammatory phase of wound healing in the skin of mice.